Defective and doped MgO monolayer as promising 2D materials for optoelectronic and spintronic applications. (October 2022) - Van On, Vo; Guerrero-Sanchez, J.; Ponce-Pérez, R.; Vu, Tuan V.; Rivas-Silva, J.F.; Cocoletzi, Gregorio H.; Hoat, D.M.
Abstract: On the basis of first-principles projector augmented wave method, the effects of point defects and doping on the MgO monolayer electronic and magnetic properties are studied. Pristine monolayer is an insulator two-dimensional (2D) material with a band gap of 3.37 eV. Various defect types including single vacancy of Mg ( V M g ) and O ( V O ), Mg+O divacancy ( V M g O ), and antisites formed by replacing one Mg atom by one O atom ( O M g ), one O atom by one Mg atom ( M g O ) and exchanging position of one Mg-O pair ( M g ↔ O ) have been considered. Material becomes ferromagnetic semiconductor upon creating a Mg single vacancy, whose magnetic properties are produced mainly by O atoms closest to the defect site. Meanwhile, the non-magnetic nature is preserved in other cases with a significant variation of the electronic band gap. Similarly, non-magnetic features are obtained when substituting one Mg atom by one Si or Ge atom ( S i M g and G e M g ). In contrast, the feature-rich half-metallicity (semiconductor spin-up state and metallic spin-down state) is induced when doping at O site ( S i O and G e O ). In these cases, magnetism is generated mainly by dopants with a small contribution from their neighbor O atoms. This work provides important insights on the MgO monolayer purposing efficient approaches to widen its working region for optoelectronic applications, as well as make it prospective to be applied as spin-filter and generate spin current in spintronic devices.